2020
DOI: 10.1186/s12879-020-4821-6
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal colonisation of women in labour with potentially pathogenic bacteria: a cross sectional study at three primary health care facilities in Central Uganda

Abstract: Background: Potentially pathogenic bacteria that colonise the lower genital tract of women in labour can be passed to the baby during birth. While many babies become colonised with these bacteria after delivery, a few develop neonatal infections. The lower genital tract is a reservoir for potential pathogens and a source of infection for neonates. We determined the prevalence of vaginal colonisation of potentially pathogenic bacteria among women in labour in Central Uganda and identified potential risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 32 publications
(33 reference statements)
2
20
0
Order By: Relevance
“…The objective was to find out any increased risk of complications like puerperal sepsis and EONS in these subsets of low-risk pregnant women. In the study, CoNS (gram-positive organism) was the most common single isolated organism whereas various studies have reported gram-negative bacteria predominantly [ 8 , 12 ]. The rate of vaginal colonization with maternal age was not found to be different in different age groups (p=0.141).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The objective was to find out any increased risk of complications like puerperal sepsis and EONS in these subsets of low-risk pregnant women. In the study, CoNS (gram-positive organism) was the most common single isolated organism whereas various studies have reported gram-negative bacteria predominantly [ 8 , 12 ]. The rate of vaginal colonization with maternal age was not found to be different in different age groups (p=0.141).…”
Section: Discussionmentioning
confidence: 99%
“…The rate of vaginal colonization with maternal age was not found to be different in different age groups (p=0.141). But few studies have reported increased colonization with age, predominantly in >30 years of age [ 8 , 12 ] and some in <20 years of age [ 13 - 14 ]. We did not find any relation between vaginal colonization and BMI (p=0.986) whereas others had found a higher BMI to be a significant risk factor for GBS colonization [ 15 - 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a cross-sectional study between July 2016 and July 2018 at three primary health care facilities in and close to Kampala in central Uganda: Mukono General Hospital (formerly Mukono Health Centre IV), Kawaala Health Centre III, and Kitebi Health Centre III [ 15 ]. This study was nested within the Chlorhexidine Trial, which is a randomized controlled assessing whether a single application of 4% chlorhexidine solution on the umbilical cord stump immediately after birth reduces the risk of omphalitis and severe illness [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…our study, a higher proportion of E. coli was reported from South Africa (45.1%), 13 Iran 56.3%), 8 and Uganda (34.5%). 25 On the other hand, the prevalence of E. coli we identified (29.9%) was higher than the prevalence reported from Nigeria (5%), 12 North-eastern India (16.3%), 26 India (19.6%), 17 Sudan (6%), 9 Spain (13%), 27 Sri Lanka (5.6%), 23 and Indonesia (3.3%). 16 The difference could be due to socioeconomic background and contamination during sample collection.…”
Section: Discussionmentioning
confidence: 66%
“…24 On the other hand, our finding was lower than the prevalence reported from Uganda (55%). 25 The discrepancies could be due to the fact that the current study considered four bacterial species as a potential pathogen for neonatal disease while the other studies considered different types and numbers of bacteria. The variations could also be due to gestational age and laboratory methods used.…”
Section: Discussionmentioning
confidence: 86%